Industrial Automation as a Service: A New Application to Industry 4.0 - Fernandes, Michel De Mattos [UNESP]; Bigheti, Jeferson Andre; Pontarolli, Ricardo Pasquati; Godoy, Eduardo Paciencia [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The fourth industrial revolution aims to achieve greater productivity, also seeking to improve the quality and efficiency of production processes. For this, the use of information and automation technologies together becomes indispensable. Collaborative automation through the sharing and use of services has been a recent paradigm in the quest to obtain a distributed, flexible and integrated on network architecture. In this article, the development of control and automation applications as a service using a Microservices Oriented Architecture is investigated. The architecture is elaborated using the Moleculer framework, which simplifies the development of microservices and applications that make up the Microservice Oriented Architecture used in this work. The development and evaluation of several services are presented, such as Data Acquisition (DAQ), Programmable Logic Controller (PLC) and PID Controller (PIDPlus). The experimental results in different scenarios demonstrated the feasibility of implementing control and automation applications as a service. A relevant advantage that this type of architecture provides is interoperability through automatic network communication between applications and microservices, which is required for Industry 4.0.
Keywords: Industrial Internet of Things; Moleculer Framework; OpenPLC; Service Oriented Architecture